2023
DOI: 10.2147/ijgm.s417066
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acupuncture and Its Related Mechanism in Treating Chronic Prostatitis/Chronic Pelvic Pain Syndrome

Hao Wang,
Jiwei Zhang,
Dongyue Ma
et al.

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is one of the most common diseases in urology, and its prevalence has been increasing, causing serious urogenital problems in men. Several targeted oral drug therapies exist to treat the pelvic pain experienced in this disease. However, these therapies may have potential adverse effects, and due to the unique location of the prostate, delivery of medications to the target lesion is difficult. Consequently, many patients seek alternative therapies. Acup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The mechanism of action is mainly to regulate neurotransmitters, inflammatory factors and immune response. [31] EA is one of the main treatment modalities, and the efficacy of EA on BPH has been gradually confirmed. Studies have shown that EA can stimulate the sacral spinal cord micturition center and excite the parasympathetic nerve to make the bladder detrusor contract and the internal sphincter open.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action is mainly to regulate neurotransmitters, inflammatory factors and immune response. [31] EA is one of the main treatment modalities, and the efficacy of EA on BPH has been gradually confirmed. Studies have shown that EA can stimulate the sacral spinal cord micturition center and excite the parasympathetic nerve to make the bladder detrusor contract and the internal sphincter open.…”
Section: Discussionmentioning
confidence: 99%
“… Mechanism of therapeutic: The mechanism of acupuncture treatment CPPS is also a research hotspot in recent years. 63 , 64 A number of experimental studies have shown that acupuncture can activate the vagus nerves, inhibit the activation of macrophages and the production of inflammatory factors, promote the production of myelin dopamine, and thereby control inflammation. The mechanism of electro-needle treatment of CPPS has attracted much attention.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is used for therapeutic or preventive purposes, in which needles are inserted into acupoints in the skin and deep tissues, and diseases are cured through the conduction effect of meridians and acupoints, which is an important part of traditional Chinese medicine [ 10 12 ]. Acupuncture reportedly can prolong ejaculation time and has a positive effect on the treatment of male sexual dysfunction, such as premature ejaculation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%